Size Matters: Endotracheal Tube Sizes and Glottic Stenosis Familiarity Among Intubating Physicians - Jason S. Chwa; Elizabeth A. Shuman; Karla O'Dell (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Given the prevalence of post‐intubation acute laryngeal injury (ALgI) and its association with glottic stenosis, greater attention has been placed on the mitigation of modifiable risk factors in patients requiring intubation, notably endotracheal tube (ETT) size. No widely accepted guidelines for adult ETT sizing exist. To better understand how factors driving ETT sizing may differ across specialties, we conducted a survey of faculty Anesthesiologists, Intensivists, and Emergency Medicine (EM) physicians. Methods An anonymous 14‐question Qualtrics survey was distributed to relevant faculty employed at a single tertiary care institution. Participants completed questions pertaining to their training, ETT sizing preferences, factors considered in decision‐making, and perceived knowledge regarding risk factors of glottic stenosis. Results A total of 103 complete responses were included, with a response rate of 55.1%. Standard ETT size was reported by 94 (91.3%) respondents to be 7.5 mm or larger in adult males and by 92 (89.3%) respondents to be 7.0 mm or larger in adult females. All respondents preferred a significantly larger ETT size for males compared to females (all p < 0.001). “Need for bronchoscopy” was the most cited factor precluding both males and females from being intubated with a smaller ETT across all specialties. When queried on posterior glottic stenosis, 64 (62.1%) respondents erroneously identified cuff pressure as a risk factor. Conclusions Understanding ETT sizing among intubating physicians is critical to reducing intubation‐related ALgI. Future laryngologist‐led interventions may be directed toward the adoption of a predominately height‐based model for ETT sizing and education on glottic stenosis. Level of Evidence 5.